Social relationships, amyloid burden, and dementia: The ARIC‐PET study - Groechel, Renée C.; Liu, Albert C.; Liu, Chelsea; Knopman, David S.; Koton, Silvia; Kucharska‐Newton, Anna M.; Lutsey, Pamela L.; Mosley, Thomas H.; Palta, Priya; Sharrett, A. Richey; Walker, Keenan A.; Wong, Dean F.; et al. (Alzheimer's & dementia : diagnosis, assessment & disease monitoring, 2024)
INTRODUCTION This study aimed to assess whether social relationships in mid‐life reduce the risk of dementia related to amyloid burden. METHODS Participants in the Atherosclerosis Risk in Communities (ARIC) study were assessed for social support and isolation (visit 2; 1990–1992). A composite measure, “social relationships,” was generated. Brain amyloid was evaluated with florbetapir positron emission tomography (PET); (visit 5; 2012–2014). Incident dementia cases were identified following visit 5 through 2019 using ongoing surveillance. Relative contributions of mid‐life social relationships and elevated brain amyloid to incident dementia were evaluated with Cox regression models. RESULTS Among 310 participants without dementia, strong mid‐life social relationships were associated independently with lower dementia risk. Elevated late‐life brain amyloid was associated with greater dementia risk. DISCUSSION Although mid‐life social relationships did not moderate the relationship between amyloid burden and dementia, these findings affirm the importance of strong social relationships as a potentially protective factor against dementia.